Health Management Students' Levels Of Critical Thinking, Submissive Behavior And Autonomy Levels - Hatice ULUSOY; Nurperihan TOSUN; Jebagı Canberk AYDIN (Association of Nurse Managers, 2016)
INTRODUCTION: The aim of this descriptive study is to identify health management students' level of critical thinking, submissive behavior and autonomy levels. METHODS: The California Critical Thinking Disposition Inventory, Submissive Behavior Scale and Autonomy sub scale of the Sociotropy/Autonomy Scale were used for data collection. In this descriptive study, sample was consisted of all the students at the Department of Health Management (N=230). Data were collected between February 18-22, 2013. In the analysis, frequency, percentage, Anova and correlation tests were used. RESULTS: Mean age of 219 students was 21,12. 27,4 % of their mothers were illiterate, 27,4% of their mothers were illiterate Total mean score of the CCTDI, Submissive Behavior and Autonomy were X=213,11+-21,62; X=36,04+-8,40 78,96+-15,19 respectively. DISCUSSION AND CONCLUSION: Female students' and 4th grade students' level of submissive behavior were lower than the other groups (p<0,05). The level of critical thinking were found to be low, and autonomy level above the moderate and submissive behavior was moderate.